Outcomes of minimal access retroperitoneal para-aortic lymphadenectomy in patients with locally advanced cervical cancer - Claire Newton; Radha Graham; Viola Liberale; Matthew Burnell; Usha Menon; Tim Mould; Adeola Olaitan; Nicola Macdonald; Martin Widschwendter; Kostas Doufekas; Mary McCormack; Anita Mitra; et al. (Journal of Obstetrics and Gynaecology)
Background To evaluate outcomes of laparoscopic retroperitoneal para-aortic lymphadenectomy for stage 1b3-3b cervical cancer.Methods Pathology databases searched for all para-aortic lymphadenectomy cases 2005–2016. Descriptive statistics were used to analyse baseline characteristics, cox models for treatment affect after accounting for variables, and Kaplan Meier curves for survival (STATA v15).Results 191 patients had 1b3-3b cervical cancer of which 110 patients had Para-aortic lymphadenectomy. 8 (7.3%) patients stage 1b3, 82 (74.6%) stage 2b, and 20 (18.1%) stage 3b cervical cancer. Mean lymph node count 11.7 (SD7.6). The intra-operative and post-operative 30 day complication rates were 8.8% (CI: 4.3%, 15.7%) and 5.3% (CI: 1.9%, 11.2%) respectively.Para-aortic nodes were apparently positive on CT/MRI in 5/110 (5%) cases. Cancer was found in 10 (8.9%, CI: 4.3%, 15.7%) cases on histology, all received extended field radiotherapy. Only 2 were identified on pre-operative CT/MRI imaging. 3 of 10 suspected node-positive cases on CT/MRI had negative histology. Para-aortic lymphadenectomy led to alteration in staging and radiotherapy management in 8 (8%, CI: 3.7%, 14.6%) patients. Mean overall survival 42.81 months (SD = 31.79 months). Survival was significantly higher for women undergoing PAN (50.57 (SD 30.7) months) compared to those who didn’t (31.27 (SD 32.5) months)Conclusion Laparoscopic retroperitoneal para-aortic lymphadenectomy is an acceptable procedure which can guide treatment in women with locally advanced cervical cancer.